Cultural determinants of health for Aboriginal and Torres Strait Islander people - a narrative overview of reviews - Ebony Verbunt; Joanne Luke; Yin Paradies; Muriel Bamblett; Connie Salamone; Amanda Jones; Margaret Kelaher (BMC, 2021)
Abstract Introduction The cultural determinants of health centre an Indigenous definition of health, and have been linked to positive health and wellbeing outcomes. There is growing evidence for the importance of the cultural determinants of health; however, to date, no high-level overview of the evidence-base has been provided. Synthesising existing literature on cultural determinants of health for Aboriginal peoples in a single manuscript will highlight what we know, and what needs to be explored in future research. It will also contribute to global efforts to capture the evidence of cultural determinant approaches amongst Indigenous populations. We therefore endeavoured to identify cultural determinants and highlight their impact on Aboriginal health and wellbeing outcomes, and outline the relationship and interconnection of different cultural determinants of health. Methods An overview of reviews was conducted. Medline (Ovid) and Scopus were searched using terms related to 'cultural determinants of health' and an 'Aboriginal definition of health'. The database search was complemented by a web-based search of grey literature. Nine reviews were retrieved and included in our overview. Results Family/community, Country and place, cultural identity and self-determination were strongly identified across reviews as having a positive impact on the health and wellbeing outcomes of Aboriginal peoples. Family/community and Country and place were found to be components of 'culture' that shaped cultural identity. Self-determination was outlined as a requirement for Aboriginal peoples to pursue their cultural, social, and economic rights. Discussion/conclusions Cultural determinants are associated with health benefits for Indigenous peoples. A causal framework, developed to discuss the relationship and interconnection of the cultural determinants of health, demonstrates that cultural identity at an individual-level is important to benefiting from other cultural determinants of health. While self-determination and connection to culture and community-controlled organisations are integral factors to increase Aboriginal resilience and resistance and improve health and wellbeing outcomes. Further research is required to shift towards a multi-level understanding of the cultural determinants of health and to develop an Indigenous-led evidence-base around causal pathways. Such a shift would ensure priorities important to Indigenous peoples are captured in policy and practice.